Clinical features and risk factors associated with acute respiratory distress syndrome in pregnant women diagnosed with COVID-19: a multi-center case-control study. (12th December 2022) - Kazemi Aski, Soudabeh; Norooznezhad, Amir Hossein; Shamshirsaz, Amir A.; Mostafaei, Shayan; Aleyasin, Ashraf; Nabavian, Seyedeh Maedeh; Alimohammadi, Shohreh; Ahangari, Roghaye; Ariana, Shideh; Ghotbizadeh, Fahimeh; Tara, Fatemeh; Pooransari, Parichehr; et al.
Abstract: Objectives: The aim of this study was to evaluate differences in clinical features and laboratory parameters in critically ill pregnant women with acute respiratory distress syndrome (ARDS) compared to moderate and severe pregnant women with coronavirus disease-2019 (COVID-19) but without ARDS. Methods: This was a retrospective multicenter study of all pregnant women with COVID-19 diagnosed with ARDS between February 15, and May 1, 2020 in nine level III maternity centers in Iran (ARDS group). The control COVID-19 pregnant women were selected from 3 of 9 level III maternity centers between March 15 and April 20, 2020. Univariate statistics were used to look at differences between groups. Cluster dendrograms were used to look at the correlations between clinical and laboratory findings in the groups. A value of p <.05 was considered statistically significant. Results: Fifteen COVID-19 infected women with ARDS were compared to 29 COVID-19 positive and ARDS negative control (moderate: ( n  = 26) 89.7% and severe: ( n  = 3)10.3%). The mean maternal age (35.6 vs. 29.4 years; p  = .002) and diagnosis of chronic hypertension (20.0% vs. 0%, p  = .034) were significantly higher in the ARDS group. There was no significant difference between the two groups in their presenting symptoms. The ARDS group had a significantly higher prevalence of tachypnea (66.6% vs. 10.3%, p  = .042) and blood oxygen saturation (SpO2 ) <93% (66.6% vs. 10.3%, p  = .004) at presentation. Relative lymphopenia (lymphocyte ratio < 10.5%, 66.6% vs. 17.2%, p  = .002), lymphocytes to leukocytes ratio (11.3% vs. 17.7%, p  = .010), and neutrophils to lymphocytes ratio (NLR) >7.5 were significantly different between the two groups (all p  < .05). Conclusion: Our data demonstrate that symptom-based strategies for identifying the critically ill pregnant women with SARS-CoV-2 are insufficient; however, vital signs and laboratory data might be helpful to predict ARDS in critically ill COVID-19 pregnant patients.